AUTOLOGOUS STEM CELL TRANSPLANTATION EXPERIENCE IN B-ALL DEVELOPING DURING MAINTENANCE LENALIDOMIDE TREATMENT:CASE REPORT - Kemal Fıdan; Gülşah Akyol; Ali Ünal; Muzaffer Keklik; Nursima Çukadar (Hematology, Transfusion and Cell Therapy, 2024)
Case report: Introduction: Secondary leukemias that occur after chemotherapy are mostly myelodysplastic syndrome and acute myeloid leukemias.With the recent increased use of immunomodulatory (IMID) drugs (pomalidomide, thalidomide and lenalidomide); It has been shown that secondary leukemias increase. Acute lymphoblastic leukemia (ALL) has frequently been described in association with IMID.Here, we present our second ASCT experience in a case who underwent autologous stem cell transplantation (ASCT) with the diagnosis of multiple myeloma and developed B-ALL during the maintenance lenalidomide treatment.Key words: Multipl myelom, B-ALL, autologous stem cell transplantation Case report: A 62-year-old female patient was diagnosed with multiple myeloma (MM) in 2017.The patient was given 4 cycles of BED (bortezomide, cyclophosphamide, dexamethasone) treatment.The patient, who was in remission, underwent ASCT with Melphalan 200 mg/m2 preparation regimen in 2018.After ASCT, the patient was started on lenalidomide maintenance treatment. Approximately 4 years later, in 2022, during the course of lenalidomide treatment, CALLA+ B-ALL was diagnosed with a bone marrow biopsy.The patient was given hyper-CVAD Chemotherapy. The patient, who was in remission after the treatment, underwent ASCT again in 2023, for the second time with the TBI + endoxan protocol (3.8 × 106/kg cells) with peripheral blood stem cells collected during the previous MM disease period. Discussion and conclusion: ALL can develop due to cytotoxic agents and immunomodulatory (IMID) drugs such as alkylating agents and topoisomerase inhibitors. Alkylating agents such as Melphalan can cause the development of AML or MDS, often through unbalanced chromosomal abnormalities from first use. The incidence of secondary ALL developing after primary malignancy is 2.3%. Secondary malignancies are a known, albeit rare, complication of long-term lenalidomide therapy. However, the incidence of secondary ALL due to lenalidomide is very low. Parrondo et al demonstrated a significant increase in the risk of secondary malignancies following lenalidomide maintenance following high-dose melphalan and autologous hematopoietic stem cell transplantation in patients with multiple myeloma (MM). 4-17% of these malignancies are hematological malignancies. After ASCT, maintenance lenalidomide has now become the standard treatment for multiple myeloma. Lenalidomide creates a basis for the development of hematological malignancy secondary to treatment in these patients. However, considering the use of melphalan in the chemotherapy regimen before ASCT, lenalidomide alone cannot be blamed for treatment-related ALL. However, as a result of our literature review, there is a stronger association between lenalidomide maintenance therapy and treatment-associated ALL in multiple myeloma patients.Therefore, in case of suspicious hematological findings in patients receiving maintenance lenalidomide treatment, bone marrow aspiration and biopsy samples should be carefully evaluated for leukemia.